Complicaciones por hemodiálisis en un Hospital de la Ciudad de Machala, Ecuador - Reyes Rueda, Elida Yesica; Garcia Maldonado, Jorge Armando; Paccha Tamay, Carmen Liliana; Vera Quiñonez, Sara Esther; Rodriguez Sotomayor, Janeth del Rosario (My University, 2021)
Introduction: Hemodialysis is a type of renal replacement therapy, indicated in patients with chronic kidney disease (CKD). These constitute a public health problem, affecting 10% of the adult population. Product of chronic non-communicable diseases (CNCD) such as arterial hypertension (HT) or diabetes mellitus (DM) among others. Aim: Identify complications during hemodialysis treatment in CKD patients. Methods: Descriptive, cross-sectional study, sample of 57 patients, older than 30 years; A validated questionnaire was carried out to collect the information. Results: Hemodialysis patients are older than 61 years in 33% of cases; of the masculine gender in 51%. With hemodialysis for more than 19 months, 72%. Complicated vertigo in 47% of cases, 30% without complications and with 5% hyperthermia and tachypnea respectively. With combined comorbidities such as diabetes + hypertension + glomerulonephritis in 19%; HBP + glomerulonephritis in 18% and glomerulonephritis in isolation in 16%. Conclusions: There is a predominance ofmales, older than 61 years in patients receiving hemodialysis. With combined comorbidities such as glomerulonephritis with high blood pressure and diabetes. Followed by the combination of glomerulonephritis with arterial hypertension and thirdly isolated glomerulonephritis. Noting that the common factor is glomerulonephritis. The most frequent complication was vertigo, followed by no complication in almost a third of the sample studied, a small percentage presented tachypnea, epistaxis, isolated or combined. The socialization of self-care in patients with diabetes and hypertension to avoid the development of chronic kidney disease is the key to its prevention
Introducción: La hemodiálisis constituye un tipo de terapia renal sustitutiva, indicado en los pacientes con Enfermedad renal crónica (ERC). Estas constituyenun problema de salud pública, afectandoal 10% de la población adulta. Producto deenfermedades crónicas no transmisibles (ECNT) como la hipertensión arterial (HTA) o la diabetes mellitus (DM)entre otros. Objetivo: Identificar las complicaciones duranteeltratamiento de hemodiálisisen pacientes con ERC.Métodos: Estudiodescriptivo, transversal,muestra de57 pacientes,mayores de 30 años;Se utilizó un cuestionario validadopara recoger la información. Resultados: Los pacientes con hemodiálisisson mayores de 61 años en 33%de los casos; del géneromasculino en 51%. Con hemodiálisispor más de 19 mesesel 72%. Complicados vértigos47%de los casos, un 30% sincomplicacionesy con un 5% hipertermiay taquipnea respectivamente. Concomorbilidades combinadas comodiabetes+HTA+glomerulonefritis en un 19%; HTA+glomerulonefritis 18% y aisladamente glomerulonefritisen un16%. Conclusiones: Existe un predominio delsexo masculino, mayores de 61años en pacientes que reciben hemodiálisis. Con comorbilidades combinadas como glomerulonefritis conhipertensión arterial y diabetes. Seguido de la combinación glomerulonefritis conhipertensión arterial y en tercer lugar glomerulonefritis aislada. Observándoseque el factor común es la glomerulonefritis. La complicaciónmás frecuente fue el vértigo, seguido de ninguna complicación en casi el tercio de la muestra estudiada, un pequeño porcentaje presentó taquipnea, epistaxis, aisladas o combinadas. La socialización del autocuidado en pacientes con diabetes eHTA paraevitar el desarrollo de la Enfermedadrenal crónica, es la clave para su prevención
Keywords: HEMODIALISIS; TERAPIA RENAL SUSTITUTIVA; ENFERMEDAD RENAL; CRONICA